Dengue in Western Terai Region of Nepal - Shah, Y; Katuwal, A; Pun, R; Pant, K; Sherchand, S P; Pandey, K; Joshi, D D; Pandey, B D (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Dengue Fever (DF) is an emerging mosquito-borne disease. It is a nagging public health problem in the low lands of Terai, expanding to new areas of Nepal in recent years. Methods: A cross-sectional study was conducted to determine anti-Dengue IgM positive rate in Mahendranagar, Dhangadi and Dang between August 2008 and November 2009. Serum samples were collected from 283 patients visiting hospitals with history of fever, headache and suspected DF. The samples were examined by ELISA. Results: The anti-Dengue IgM positivity was found to be 9.8 %. The positive rate was highest in Mahendranagar (13.3 %) followed by Dhangadi (9.8 %) (P<0.05). The Dengue positive cases were higher in female (10.9 %) than males (9.0 %). The positivity was higher in Ethnic group Brahman/Chherti (13.1%) as compared to Janajati (5.6 %). The highest positive cases (10.7 %) were from age group above 50 years. The highest numbers of Dengue positive cases were observed in occupation group of agriculture (18.2 %) (P>0.05). Conclusions: Dengue has substantial expansion in Western and Far Western Terai region of Nepal which was limited to the middle Terai region in the past and mostly infects older people. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Â Keywords:<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> dengue fever; IgM ELISA; terai region.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>